Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/jsfa.1049
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain fatty acid content in the hindgut of rats fed various composite foods and commercial dietary fibre fractions from similar sources

Abstract: The fermentability of indigestible carbohydrates and content of short-chain fatty acids along the hindgut of rats were investigated using plant materials of importance in the Swedish diet (instant potato powder, apples and oat¯akes). Results with the composite food products were compared with commercial ®bre fractions obtained from similar sources, ie potato ®bre, apple pectin and b-glucanenriched oat ®bre. The materials were incorporated into diets yielding a concentration of 60 or 70 g kg À1 indigestible car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
(39 reference statements)
8
18
1
1
Order By: Relevance
“…The high caecal proportion of butyric acid on the apple pulp diets may be due to the differences in fibre matrix (Henningsson et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high caecal proportion of butyric acid on the apple pulp diets may be due to the differences in fibre matrix (Henningsson et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The potato products gave high concentrations of butyric acid. This may be explained by the fact that some resistant starch could be present in those products and was fermented to butyric acid, as was shown in pigs (Martin et al, 1998;Henningsson et al, 2002). One of the most important properties of the SCFA is their trophic effect on the intestinal epithelium, with butyric acid considered to be the most effective and propionic acid, the least.…”
Section: Resultsmentioning
confidence: 99%
“…SCFAs may also have metabolic effects and it has been shown that propionic acid may inhibit the synthesis of cholesterol in the liver (Wolever et al, 1991;Stark and Madar, 1993). Different types of carbohydrates give rise to different amounts and patterns of SCFAs, and factors that may play a role are the composition and the molecular weight of the carbohydrates (Berggren et al, 1993;Henningsson et al, 2002a). In order to evaluate the effects of dietary components on the production of SCFAs in healthy subjects and in patients suffering of colonic diseases, it is crucial to have an efficient and inexpensive analytical method that enables the identification and quantification of the SCFA in various body fluids such as faeces.…”
Section: Introductionmentioning
confidence: 99%
“…La consommation journalière de plusieurs pommes peut pratiquement placer ce fruit parmi les sources majeures de fibres, auxquelles appartiennent aussi les produits céréaliers et les légumineuses. Dans des expériences menées chez l'animal, il a été montré que la fraction de fibres ou des extraits lyophilisés de pomme favorise nettement les fermentations butyriques [8,28,41]. Il est difficile de situer la fraction responsable de ce type d'orientation fermentaire, mais il ne s'agit pas vraisemblablement de la pectine elle-même qui favorise plutôt des fermentations riches en acide acétique [8].…”
Section: Impact Sur Les Fermentations Digestives Dans Le Côlonunclassified